Modest attenuation of HIV-1 Vpu alleles derived from elite controller plasma - Chen, Jingyan; Tibroni, Nadine; Galaski, Johanna; Müller, Birthe; Haller, Claudia; Fackler, Oliver Till (PLOS ONE, 2015)
In the absence of antiretroviral therapy, infection with human immunodeficiency virus type 1 (HIV-1) can typically not be controlled by the infected host and results in the development of acquired immunodeficiency. In rare cases, however, patients spontaneously control HIV-1 replication. Mechanisms by which such elite controllers (ECs) achieve control of HIV-1 replication include particularly efficient immune responses as well as reduced fitness of the specific virus strains. To address whether polymorphisms in the accessory HIV-1 protein Vpu are associated with EC status we functionally analyzed a panel of plasma-derived vpu alleles from 15 EC and 16 chronic progressor (CP) patients. Antagonism of the HIV particle release restriction by the intrinsic immunity factor CD317/tetherin was well conserved among EC and CP Vpu alleles, underscoring the selective advantage of this Vpu function in HIV-1 infected individuals. In contrast, interference with CD317/tetherin induced NF-κB activation was little conserved in both groups. EC Vpus more frequently displayed reduced ability to downregulate cell surface levels of CD4 and MHC class I (MHC-I) molecules as well as of the NK cell ligand NTB-A. Polymorphisms potentially associated with high affinity interactions of the inhibitory killer immunoglobulin-like receptor (KIR) KIR2DL2 were significantly enriched among EC Vpus but did not account for these functional differences. Together these results suggest that in a subgroup of EC patients, some Vpu functions are modestly reduced, possibly as a result of host selection.
Gesehen am 23.08.2017